P93 Semi-mechanistic modelling of hydrocortisone pharmacokinetics in paediatric patients with adrenal insufficiency. Issue 6 (17th May 2019) - Stachanow, V; Melin, J; Michelet, R; Blankenstein, O; Neumann, U; Ross, R; Whitaker, M; Huisinga, W; Kloft, C
Abstract : Background: Patients with congenital adrenal hyperplasia (CAH) have low to no biosynthesis of cortisol and require lifelong cortisol replacement. Optimisation of hydrocortisone (HC, synthetic cortisol) therapy in this population is important, since too low or high cortisol concentrations increase the risk of adrenal crisis or Cushing's syndrome 1 . HC has nonlinear pharmacokinetics (PK) caused by saturable binding to corticosteroid binding globulin (CBG) 2 . The objective of this analysis was to extend an established paediatric HC PK-model 3 with dried blood spot (DBS) data in order to further characterise the binding behaviour of HC in children. Methods: A semi-mechanistic adult PK model for a novel HC formulation 4 has previously been reduced to a paediatric model using sparse plasma samples from a phase III study in 24 patients with adrenal insufficiency 5 . Plasma and DBS concentrations of cortisol were collected and additional DBS HC concentrations were obtained from a follow-up study. The relation between plasma and DBS samples was characterised by a graphical evaluation, after which nonlinear mixed-effects modelling was applied using NONMEM 7.4. Results: Plasma concentrations of cortisol were substantially higher than the corresponding DBS concentrations. The plasma/DBS ratio ranged between 2 to 8 within and between children, while the relation between the cortisol DBS concentrations and cortisol plasma concentrations showed nonlinear behaviour mirroring the nonlinear binding kinetics to CBG. Conclusions: Our graphical analysis identified substantial differences and high inter- and intraindividual variabilities between plasma and DBS samples. A nonlinear mixed-effects model is being set up to quantify these findings and allow for further prediction of HC exposure. Afterwards, effect biomarkers can be included in order to evaluate cortisol replacement therapy and to optimise the HC treatment in paediatric patients. References: Speiser PW, et al. J Clin Endocrinol Metab 2010;95(9):4133–4160. Lentjes EG, WM, et al: J Clin Endocrinol Metab . 1999;84(2):682–687. Melin J:Dissertation 2017. Melin J, et al: Clin Pharmacokinet . 2018;57(4):515–527. Neumann U. et al: Clin Endocrinol . 2018;88(1):21–29. Disclosure(s): Nothing to disclose